More transcontinental mislabeling in the genus Onthophagus: d’Orbigny’s “African” Group 27 (Coleoptera: Scarabaeidae: Scarabaeinae) - Rossini, M.; Vaz-De-Mello, F. Z.; Zunino, M. (Zootaxa, 2016)
With more than 2300 species, Onthophagus Latreille, 1802 is a mega diverse genus within the subfamily Scarabaeinae. Recent revisions have yielded an over-abundance of redundant species names accumulated over the years as results of bad and inappropriate taxonomic practices. Indeed, the difficulty of access to public entomological collections, the usage of outdated bibliographic references, as well as the description of new species based on a few specimens, and often accompanied by diagnoses largely vague, has resulted thus far in a very large number of synonyms.